Meningkatkan Motivasi Belajar Al-Qur’an Surat At-Tin Siswa Kelas IV Melalui Model Cooperatif Learning - Syarmaiweli, Syarmaiweli (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to analyze the improvement of learning outcomes of 4th-grade students at SD Negeri 05 Guguak Malintang by applying the Cooperative Learning model to the material of Q.S. At-Tin. The research was conducted in two cycles using observation and test techniques as data collection instruments. The results showed a significant improvement in student activity and test scores in cycle II, with a learning completion percentage reaching 94.73%. This indicates that the implementation of the Cooperative Learning model can enhance students’ motivation and learning outcomes. The increase in student activity in cycle II is reflected in the reduction of students in the "Poor" category and the improvement in the "Good" and "Very Good" categories.